(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
World War II began on September 1, 1939. The same German troops invaded Poland from three directions they entered. The war soon engulfed many nations around the world. On June 22, 1941, 191 Nazi divisions (153 of which were directly owned by Germany) From the Baltic Sea of the USSR to the Black Sea region closed in on the border and attacked. Thus, in the history of the world, the human ear has never heard or seen with the eyes the tragedy began. Much has been written about the outbreak of World War II, its causes and culprits